Evaluating the Knowledge, Attitudes and Practices of Medical Laboratory Professionals Towards Implementing Enterprise Risk Management in Harare, Zimbabwe: A Cross‐Sectional Study - Donald Vhanda; Judy Mwenje; Reynold Vhanda; Kudzai Chinowaita; Itai James Blessing Chitungo; Tafadzwa Dzinamarira (Health Science Reports, 2025)
ABSTRACT Background and Aims Medical laboratories play a crucial role in healthcare, with the majority of medical judgements based on clinical laboratory testing outcomes. Therefore, laboratories must provide accurate, timely, reliable, and interpretable diagnostic results that inform patient care. However, laboratory operations are characteristically vulnerable to complex and interdependent risks, including errors in testing, biosafety and biosecurity breaches, equipment malfunctions, regulatory and compliance issues, and financial concerns. Enterprise Risk Management (ERM) is a holistic approach that identifies, assesses, mitigates these risks and identifies opportunities to ensure patient safety, laboratory quality, and organisational sustainability. This study evaluated the knowledge, attitudes, and practices (KAP) of the medical laboratory professionals towards the implementation ERM in Harare, Zimbabwe. Methods The study design was cross‐sectional, involving 41 questionnaires and interviews which were self‐administered to participants in the medical laboratories in Harare, Zimbabwe. The questionnaires assessed the knowledge, attitude and practice of ERM implementation by interrogating known ERM elements. Statistical Package for Social Sciences (SPSS) version 22 was used for data analysis. Results ERM culture and ERM best practices were strongly correlated (0.735). Crobach's alpha coefficients of 0.89 and 0.92 were obtained showing internal consistency. Six out of nine ERM hard aspects were missing at the time of assessment. The mean score for the soft aspects of ERM was 3.3 and the risk culture rating was 2.81 out of a scale of 5. Conclusion The risk culture did not support ERM implementation. The knowledge, attitude and practices show risk immaturity. ERM knowledge gaps exist among medical laboratory professionals. The study highlights the need for targeted training and awareness programs to enhance ERM knowledge and attitude among laboratory professionals.